Strategies Implemented by Public Institutions to Approach the Judicialization of Health Care in Brazil: A Systematic Scoping Review - Yamauti, Sueli Miyuki; Barreto, Jorge Otavio Maia; Barberato-Filho, Silvio; Lopes, Luciane Cruz (Frontiers in Pharmacology, 2020)
Background: The judicialization of health care is a social claim concerning the right to the access to health care. It usually occurs due to gaps in public policy or failures in its application. In Brazil, several public institutions have implemented strategies to approach this phenomenon. However, these strategies have not yet been systematized into functional categories. Objective: To categorize and analyze the strategies implemented by public institutions in Brazil to approach the judicialization of health care. Method: A systematic scoping review was developed following the method proposed by the Joanna Briggs Institute. The descriptor ‘judicialization of health’ was used to conduct the searches for studies in 18 electronic databases and other types of documents in the gray literature until March 2019. Documents containing the reports of strategies implemented in public institutions to approach the judicialization of health care in Brazil were included. Two independent reviewers assessed the eligibility of the documents and extracted the data. The strategies identified were categorized using definitions from the World Health Organization and existing Brazilian legislation. Results: 78 implemented strategies were identified and organized into nine categories: i. Technical support to the judiciary; ii. State health committees; iii. Organization of assistance; iv. Compliance with court orders, v. Computerized information systems; vi. Administrative proceeding; vii. Defense of the public authority; viii. Pharmacy and therapeutics committee; ix. Alternative dispute resolution. These categories are not mutually exclusive and often act in concert or complement each other’s activities. They represent services either existing or provided for in legal provisions by the public administration to meet various types of demands. Conclusions: The categories proposed to approach the judicialization of health care represent some of the recommendations for qualifying public administration or are provided for in Brazilian legislation, or both. The existence of recommendations and legislation facilitate, but do not guarantee, the implementation of strategies by public institutions.